Health care transition quadruple aim outcomes for IDD: Scoping review - Ellen Fremion; Kathleen Irby; Sophia Jan; Carlie Stein Somerville; Susan Shanske; Dava Szalda; Ahmet Uluer; Parag Shah (Health Care Transitions)
Purpose: Structured HCT models addressing planning, transfer, and integration into adult care for adolescents and young adults with childhood-acquired chronic conditions are becoming more prevalent. However, consensus on outcome measures to assess health care transition (HCT) interventions particularly for intellectual and developmental disabilities (IDD) population is lacking. This scoping review identified potential HCT outcome measures for young adults (aged 18–26) with IDD using the Quadruple Aim Framework. Methods: On August 6, 2021 and April 27, 2023, Medline Ovid, Embase, Web of Science, PsycINFO, and Cochrane databases were searched using the terms “young adult,” “intellectual disability,” “developmental disability, “cognitive dysfunction,” “autism,” “cerebral palsy,” “spina bifida,” and “transition to adult care.” Searches were limited to publications in English and published from 2000 to present. Observational and experimental (qualitative or quantitative) studies were included if participants were young adults (median/mean ages 18–26) with IDD (Autism, cerebral palsy, Down syndrome, spina bifida, or other IDD-related conditions) and study outcomes addressed one of the Quadruple Aim domains (population health, patient/family experience, cost/utilization, and healthcare provider/caregiver experience). Studies were excluded if participants had attention deficit/hyperactivity disorder or learning disability only, if outcomes were primarily educational or vocational, or if publications were reviews, abstracts, or not in English. Results: One hundred and three articles were included data extraction. Articles were categorized under the Quadruple Aim domains: Population Health (43), Patient/Caregiver Healthcare Experience included (23), Cost/Utilization (24), and Healthcare Provider/Caregiver Experience (15). Most articles were observational and utilized a variety of assessments or internally developed questions as measures. Conclusions: While studies describing HCT outcomes for the IDD population are limited and measures are inconsistent, studies pertaining to Quadruple Aim outcomes identified in this review can further direct efforts towards consensus and standardization of HCT outcome measures to address the needs of individuals with IDD, their families, and caregivers/providers.